An Assessment of Rural Youth Participation in Community Development Projects in Turkana South Sub-County: An Approach to Community Development and Sustainable Development - Ochieng, Otieno Evans; Onyango, Maria Adhiambo; Kinaro, Zachary Omambia (East African Nature & Science Organization, 2020)
The integration of local and international cultures enhances people’s ability to adapt to external influences of sustainable aid and sustainable development programs and processes. The study was conducted in Turkana, where government intervention on projects was made with deliberate efforts to implement inclusive development projects. Traditionally Turkana society has well-defined gender roles that appear to contradict inclusive and participatory approaches determined by government projects and interventions. The study sought to establish a legitimate influence on youth participation and to assess the impact of cultural norms on youth participation in community projects. The study used a descriptive design and targeted 47,359 young people. The study used Krejecie and Morgan’s table and an equally divided sample procedure to obtain a sample of 381 respondents in the study. Research has shown that educated youth will speak well and seek citizenship, and show that the standard of formal education is negatively correlated (-0251) with youth participation in project planning and community development projects (-0.094) respectively, barriers to youth participation in project planning are not limited to learning and training. Therefore, political, institutional, financial and technical factors played out in determining whose voice is heard and which decisions are acceptable. There was an inconsistent balance (-0.109) between gender roles and participation in community project planning meetings and gender issues consideration in community projects, respectively. A negative correlation (-0.14) between age and meeting planning has been revealed which means that the patriarchal values system in rural areas favours gender roles and traditional cultural practices that oppose the development, advancement and participation of women in community development
Keywords: Rural Youth Participation,; Community Development,; Education Level,; Cultural Value